Exploring the constructions of transparency, animal sentience and culture of care in animal research - Cantrell, J (2022)
Animal research remains an important part of science with 2.88 million procedures being carried in 2019 in the UK. Although the number of animals used is declining each year, this is still a significant level of animal use at a time when our understanding of animal sentience is ever increasing. This research work explores the construction of important issues such as open science, animal sentience and culture of care and how these are potentially being seen in terms of animal research ethics responsibilities. Through the lens of empirical ethics, this study explores various actors’ awareness and construction of animal sentience, transparency in reporting standards, and perceptions of a culture of care. Previous studies have focused on these, though little research has been done to examine how institutions respond to the transparency agenda and then link this to researchers’ views of animal sentience and culture of care. This study is being conducted at an important time when the UK government has asked for a public policy review of the current standing on animal usage in research and alongside the introduction of new UK animal welfare legislation which formal recognises animals as sentient.